Embracing Community-Centric Careers in a Post-Barbie World: Navigating Identity, Expectations, and Impact in Medicine and Veterinary Medicine - Carmel Falek; Cecilia Joshi; Minna Ng (The University of Alabama, 2024)
Navigating the intersection between personal aspirations and societal expectations poses a significant challenge. We as college students share our transformative journey toward embracing community-centric career paths in medicine and veterinary medicine amid the expectations of attending a prestigious institution. Through an educational neuroscience service-learning course led by Dr. Minna Ng, we partnered with our local YMCA AfterSchool Program, designing neuroscience-based activities and forging meaningful connections with students. Reflecting on our experiences, we challenge stereotypes surrounding "prestigious" specialties and female-dominated fields. We underscore the importance of aligning career aspirations with personal values and passions while celebrating the inherent value of community-centric professions within medical fields.